An unusual case of foreign body aspiration mimicking cavitary tuberculosis in adolescent patient: Thread aspiration - Cakir Erkan; Torun Emel; Uyan Zeynep; Akca Ozge; Soysal Omer (BMC, 2012)
Abstract Foreign body aspiration continues to be a serious problem in childhood and adolescent period with significant rate of morbidity and rarely mortality. Half of the foreign body aspiration cases have no history of aspiration. The main foreign bodies inhaled are food fragments and different kinds of metallic objects. A 12-year-old girl was referred to the pediatric pulmonology department for chronic cough and hemoptysis. She had persistent infiltration and cavitary lesion mimicking cavitary tuberculosis. There was no contact history with tuberculosis in her family and acid resistant bacillus was not found in the sputum examination. Flexible bronchoscopy was performed for persistent infiltration and hemoptysis and inflamed thread was found in right lower lobe bronchus. This is the first case of thread inhalation mimicking cavitary tuberculosis in an adolescent patient.